SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT KEJIWAAN BIPOLAR DENGAN MENGGUNAKAN METODE BAYESIAN NETWORK - Olivia Prima Putri; Chairisni Lubis; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Expert System is one of artificial Intelligence which uses the knowledge of an expert as its knowledge base. In this research, expert system  designed to diagnosing bipolar disorder  using the method of bayesian network. The result of this application is  the type of psychiatric diseases  bipolar and the value of the probability of each disease. In this research, the  probability of bipolar disorder test data according to medical records obtained yield was 39.39% and the results of testing using test data with new symptoms obtained yield was 55.55%. Key words Bayesian network, bipolar disorder,expert system